Anion-templated assembly of multinuclear copper(ii)–triazole complexes. (5th August 2020) - Gopalakrishnan, Mohan; Krittametaporn, Nuttaporn; Yoshinari, Nobuto; Konno, Takumi; Sangtrirutnugul, Preeyanuch
Abstract : Anions were used as templates to construct copper(ii ) clusters with different architectures. Abstract : The reactions of [Cu(CH3 CN)4 ]PF6 and Cu(ClO4 )2 with (1-benzyl-1 H -1, 2, 3-triazol-4-yl)(pyridin-2-yl)phenylmethanol (Hpytm) in a 1 : 1 ratio under aerobic conditions afforded [Cu6 (pytm)6 (SiF6 )](SiF6 )2 (1 ) and [Cu3 (pytm)3 (MeOH)(ClO4 )](ClO4 )2 n (2 ), respectively. Single-crystal X-ray crystallography reveals that both compounds contain the trinuclear, six-membered Cu II cluster, [CuII3(μ2 -κ 3 - N, O, N ′-pytm)3 ] 3+, as a building block. In 1, the two trinuclear clusters sandwich an SiF6 2− anion to form a discrete dimeric hexanuclear structure, whereas in 2 the Cu II clusters are linked by ClO4 − anions in a one-dimensional polymeric structure. Magnetic susceptibility measurements indicate that a relatively large antiferromagnetic coupling exists in each trinuclear cluster in 1 and 2, with the J values of −48.2(4) cm −1 and −69.2(2) cm −1, respectively. In addition, weak yet non-negligible magnetic interactions between two CuII3 cluster units were observed for both complexes.